2005
DOI: 10.2323/jgam.51.287
|View full text |Cite
|
Sign up to set email alerts
|

Reclassification of Methylobacterium chloromethanicum and Methylobacterium dichloromethanicum as later subjective synonyms of Methylobacterium extorquens and of Methylobacterium lusitanum as a later subjective synonym of Methylobacterium rhodesianum

Abstract: Phylogenetic analysis based on 16S rDNA sequences was performed on all type strains of the 14 validly described Methylobacterium species to ascertain the genealogic relationships among these species. The results showed that type strains of Methylobacterium were divided into two monophyletic groups whose members were distinct species with sequence similarity values greater than 97.0% between any two of the members in the same group. Only M. organophilum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 32 publications
3
31
0
Order By: Relevance
“…rhodesianum. These results were supported by previously reported DNA-DNA hybridization data (Kato et al, 2005), which showed that Methylobacterium chloromethanicum and Methylobacterium dichloromethanicum were later heterotypic synonyms of Methylobacterium extorquens and that Methylobacterium lusitanum was a later heterotypic synonym of Methylobacterium rhodesianum. It was found that phylogenetic analysis using gyrB sequences was a useful index to classify and identify Methylobacterium species, and agreed with DNA-DNA relatedness data.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…rhodesianum. These results were supported by previously reported DNA-DNA hybridization data (Kato et al, 2005), which showed that Methylobacterium chloromethanicum and Methylobacterium dichloromethanicum were later heterotypic synonyms of Methylobacterium extorquens and that Methylobacterium lusitanum was a later heterotypic synonym of Methylobacterium rhodesianum. It was found that phylogenetic analysis using gyrB sequences was a useful index to classify and identify Methylobacterium species, and agreed with DNA-DNA relatedness data.…”
supporting
confidence: 82%
“…The 16S rRNA gene was analysed as described by Kato et al (2005). gyrB gene sequences were determined directly from PCR fragments using the method described by Yamamoto & Harayama (1995) and Kasai et al (2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Aurantimonas has been recently established (Denner et al, 2003), and the biology of this genus in relation to the plant symbiosis is largely unknown, and needs to conduct further study. Methylobacterium chloromethanicum is currently considered as a synonym of Methylobacterium extorquens (Kato et al, 2005). Several Methylobacterium spp., including M. extorquens, are well-known plant-associated bacteria (Corpe, 1985) as both an epiphyte and an endophyte, and the scavenging monocarbon wastes such as methanol in plant tissues is speculated for the putative role of this bacterial group (Corpe and Basil, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Major cellular fatty acids are C 18 : 1 v7c, C 18 : 0 and C 16 : 0 . Tani et al, 2012b); 4, Methylobacterium organophilum JCM 2833 T (Kato et al 2005); 5, Methylobacterium marchantiae JT1 T ; 6, Methylobacterium bullatum F3.2 T (Hoppe et al, 2011); 7, Methylobacterium jeotgali S2R03-9 T (Aslam et al 2007); 8, Methylobacterium cerastii C15 T (Wellner et al, 2012); 9, Methylobacterium gossipiicola Gh-105 T (Madhaiyan et al, 2012); 10, Methylobacterium phyllosphaerae CBMB27 T (Madhaiyan et al, 2009); 11, Methylobacterium platani PMB02 T (Kang et al, 2007); and 12, Methylobacterium oxalidis 35a T (Tani et al, 2012a). +, Positive; 2, negative; (+), weakly positive; NA, data not available; V, variable reaction; *, data from this study.…”
Section: Description Of Methylobacterium Haplocladii Sp Novmentioning
confidence: 99%